Role of NEP in Reskilling the Youth for Reaping Demographic Dividend in India A Critical Analysis - Shukla, Neha; Pahwa, Sonal (JOURNAL OF INDIAN EDUCATION, 2020)
With a large pool of skilled people, India has an opportunity to become a skill provider for the world, particularly the ageing developed world”, as quoted by Pradhan Mantri Kaushal Vikas Yojana. Policy makers have the intention of encashing population dividend and driving the country’s growth not by natural resources but by knowledge resources. To achieve global competitiveness, India should nurture the human capital. Despite having a huge population base and substantial efforts being laid on education and training, our employability index is not showing much positive signs and we still face the scarcity of skilled human resource. Moreover, with the increasing automation certain skill sets would become redundant and thus our education system needs to focus on what we need to learn and what is best left to machines. This knowledge paper attempts to analyse the current skill gap, delve into the provisions given in National Education Policy (NEP) 2020, with respect to skill development and explore the possible interventions to fill the gap in skill ecosystem. It also aims to evaluate the existing employability gaps and highlight suggestive interventions through the new NEP.